Sarcoidosis in Jordan: A Study of the Clinical Phenotype and Disease Outcome - Fatima ALNAIMAT; Khaled AL OWEIDAT; Anas ALRWASHDEH; Ahmad ALNASHRATI; Saba BARHAM; Mohammad HIJAZ; Dina MURAD; Sameeha ALSHELLEH; Nathir OBEIDAT (Archives of Rheumatology, 2020)
Objectives: This study aims to evaluate the clinical phenotypic features of sarcoidosis in a single-center academic hospital in Jordan. Patients and methods: A retrospective file review was performed at an academic medical center in Jordan that included all patients diagnosed with sarcoidosis between January 2000 and December 2018. A total of 150 patients with sarcoidosis (38 males, 112 females; mean age 47.8±11.7 years; range, 17 to 79 years) were evaluated. Clinical data extracted from the files included the sex of the patient, the age at time of diagnosis, diagnosis date, the season during which the diagnosis was established, and smoking history. Biopsy histopathology, spirometry, nerve conduction, echocardiography, and imaging reports including plain radiographs, ultrasonographic, magnetic resonance and computed tomography reports were reviewed. Data including laboratory values, medication usage, clinical outcomes, and morbidity/mortality were collected. Pulmonary function tests including spirometry and lung volumes along with the diffusing capacity for carbon monoxide were reviewed for the presence of restriction, obstruction or reduction in the diffusion capacity of carbon monoxide. Identification of extra-thoracic organ involvement was determined in each patient in accordance with the criteria suggested by the updated World Association of Sarcoidosis and Other Granulomatous Disorders. Results: A total of 77.3% of the patients were diagnosed by biopsy. One case of Lofgren’s syndrome was identified. Of the patients, 18.0% had isolated pulmonary sarcoidosis, 75.3% had pulmonary and extra-pulmonary sarcoidosis and 6.7% had isolated extra-pulmonary sarcoidosis while 81.3% had respiratory symptoms, mostly shortness of breath and cough. Extra-thoracic organ involvement mostly involved the musculoskeletal system (33%) followed by the skin (20%). Female patients had more extra-thoracic involvement but the sex difference was only statistically significant for cutaneous involvement. Of the patients, 84% received treatment while 20% had disease remission during the first two years after diagnosis and 70% required treatment beyond two years after diagnosis. Conclusion: Various sarcoidosis clinical phenotypes are seen among Jordanian patients. Jordanian females are more affected by the disease and have more extra-thoracic involvement compared to male patients. A large number of the study patients received treatment.